Concrete Quality Control on Rigid Pavement in The Petamanan - Sidomulyo Road Rehabilitation Project Limpung Sub-District Batang District - Jamal, Jamal; Rizal, Zahrul; Ian, M. Rezki; Prasetyo, Rendy (Portal: Jurnal Teknik Sipil, 2025)
The implementation of rigid pavement construction, in fact, has concrete quality results that do not meet the applicable criteria or specifications so that concrete work on rigid pavement can experience cracks or concrete fractures. The research was conducted by direct observation in the field and collecting laboratory testing data, then analyzing by comparing the results of concrete work against the Indonesian National Standard (SNI) and the acceptance of concrete quality based on the 2018 Bina Marga General Specifications (Revision 2) on the Petamanan - Sidomulyo Road Rehabilitation project, Limpung District, Batang Regency. The results showed that the Job Mix Formula (JMF) used in the field produced slump values that met the criteria. The level of uniformity of the quality of concrete implementation on the results of the bending strength of the beam shows the value of the standard deviation with the classification of "excellent" and the level of variation is included in the classification of "very good". The conclusion from the calculation shows that the flexural strength of the beam samples during implementation at each station meets the specification fs'45 kg/cm2 (4.41Mpa) at the age of 28 days.